Penalaran Analogi Peserta Didik SMP Kemampuan Matematika Rendah dalam Menyelesaikan Masalah Open-Ended Topik Aljabar - Ain, Zulfa Qurrotu; Masriyah; Yurizka Melia Sari (MATHEdunesa, 2026)
Analogical reasoning is a person's thought process to draw conclusions by processing information and identifying factual relationships so that it can be used to solve problems. Analogical reasoning is important in solving mathematical problems. However, some studies show that analogical reasoning in low mathematics ability students still requires in-depth research, especially in solving problems. This study aims to describe the analogical reasoning of low mathematics ability students in solving open-ended problems on algebra topics. This study used a qualitative method with a case study approach, in which data were obtained through tests and interviews with one eighth-grade student with low mathematical ability. The subject was selected based on mathematical ability, communication skills, and problem-solving skills. Analogical reasoning was analyzed based on four stages according to Ruppert: structuring, mapping, applying, and verifying. The results of the analysis show that students with low mathematical ability only identify some of the information in the structuring stage, do not find similarities in structure in the mapping stage, use the wrong solution strategy in the applying stage, and do not check the solution in the verifying stage. This research is expected to lead to further studies that can explore analogical reasoning on various topics, classes, reviews, mathematics ability levels, and other open-ended problem categories to gain a deeper understanding of students' analogical reasoning.